Qur'anic Readings and Modern Arabic Dialects: A Descriptive-Comparative Linguistic Study - Al Sabahi, Rushdi; Elbanna, Mariam; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2026)
This study aims to explore the phonological relationship between Qur'anic readings (qirā'āt) and modern Arabic dialects by examining how variations in the recitations reflect the diversity of Arabic pronunciation from the early Islamic period to the present. Grounded in historical linguistics and sociolinguistic theory, the research views the qirā'āt as linguistic evidence of early Arabic dialectal diversity and as a foundation for understanding the development of spoken Arabic. It draws upon classical works such as Ibn Mujāhid's Al-Sab'ah fī al-Qirā'āt and Ibn al-Jazarī's Al-Nashr fī al-Qirā'āt al-'Ashr, alongside the contributions of modern linguists such as Tammam Hassan and Ahmed Mukhtar Omar, who have highlighted the linguistic significance of the qirā'āt, noting that few studies have directly compared these phonological features with those of contemporary dialects. Employing a descriptive, analytical, and comparative linguistic approach, the study examines phonetic phenomena such as imālah (vowel fronting), tashīl al-hamz (glottal easing), idghām (assimilation), and ibdāl (substitution) across Qur'anic readings and modern dialects. The findings reveal direct correspondences between certain phonetic traits in present-day dialects-such as the softening of the glottal stop and vowel fronting-and patterns documented in the qirā'āt. This connection underscores the historical continuity of the Arabic language and provides valuable linguistic insights for Qur'anic and phonological studies. The novelty of this research lies in its unique integration of Qur'anic phonology and modern dialectology, demonstrating that the qirā'āt preserve ancient dialectal features that remain alive in contemporary spoken Arabic.